PENGARUH HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN COFFEE SHOP JELANG SORE DI KOTA BALIKPAPAN - Rosmiah Jamalia; Annisa Wahyuni Arsyad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of price, product quality, and service quality on purchasing decisions among consumers of Coffee Shop Jelang Sore in Balikpapan City. The research employed a quantitative approach using a causal research design. The population consisted of consumers who had purchased products from Coffee Shop Jelang Sore, with a sample of 120 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS. Prior to hypothesis testing, the data were subjected to validity, reliability, and classical assumption tests. The findings indicate that price, product quality, and service quality each have a positive and significant effect on purchasing decisions. Simultaneously, these three independent variables also significantly influence purchasing decisions. The correlation coefficient (R) of 0.734 indicates a strong positive relationship between the independent variables and purchasing decisions. These findings suggest that maintaining competitive prices, improving product quality, and delivering excellent service are essential strategies for increasing consumers' purchasing decisions at Coffee Shop Jelang Sore in Balikpapan City.